2001
DOI: 10.1007/s002230001210
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in Regional Bone Mineral Density in Healthy Chinese: Age-Related and Sex-Dependent

Abstract: To investigate the pattern of age-related and sex-dependent bone mineral density (BMD) changes in the six skeletal regions in healthy Chinese, total-body and regional BMD were measured by dual-energy X-ray absorptiometry (DXA) in 310 women and 387 men aged 20-80 years. In women, a five-phase change was discernible in the axial bones: (1) gradual bone increase from 20-29 years old to maximal BMD at 35-39 years old; (2) maintenance of this level from 35-39 to 40-44; (3) a mild bone decrease from 40-44 to 45-49; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Consistent with previous reports, our results concerning hormonal changes showed that TT, FT and DHEAS levels were negatively, and LH and FSH levels were positively correlated with age. Age-related decrease in BMD of different body regions have been shown in several studies [2,7,14,29,30]. In our study, BMD measurement results were consistent with the previous reports.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with previous reports, our results concerning hormonal changes showed that TT, FT and DHEAS levels were negatively, and LH and FSH levels were positively correlated with age. Age-related decrease in BMD of different body regions have been shown in several studies [2,7,14,29,30]. In our study, BMD measurement results were consistent with the previous reports.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, BMD measurement results were consistent with the previous reports. Femoral neck BMD showed a slight decrease with age, whereas L 2 -L 4 vertebrae appeared to increase; this result is most likely a consequence of anteroposterior projection of DXA, in which degenerative changes in the posterior spinous elements may be misleading [7,14,29,30].…”
Section: Discussionmentioning
confidence: 92%
“…The basic characteristics of the children are summarized in Table 1. All children were female and 31.4 ± 5.8 years of age, that is, the time when PBD is achieved or maintained in Chinese women (57) . All the subjects were genotyped at the Pvu II and Xba I polymorphic sites.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a person's facial shape, bone thickness, and bone density are related to their sex (Ferrario et al, 1993;Yao et al, 2001) and age (Enlow, 1966;Bartlett et al, 1992;Burt and Perrett, 1995;Mendelson and Wong, 2012), and the speed of sound through some facial bones is known to vary by age (Rose et al, 2001). Demographic characteristics also affect the vocal apparatus and phonation.…”
Section: B Demographicsmentioning
confidence: 95%